Eccentric movements of temporomandibular joint and upper airway volume: Three-dimensional segmentation using cone beam computed tomography - Costa, Andre Luiz Ferreira; Castilho Fardim, Karolina Aparecida; de Almeida, Bruna Maciel; Gomes, João Pedro Perez; Braz-Silva, Paulo Henrique; Dieguez, Flávia Limberg; Cardoso, Cristiane de Almeida Baldini; Araki, Angela Toshie; de Castro Lopes, Sérgio Lucio Pereira (Cranio, 2024)
The purpose of the present investigation was to assess whether possible changes in the dynamic movements of the TMJ might cause a greater variation between the volumes of the upper airways in open- and closed-mouth positions. CBCT scans of 92 subjects were used to assess the TMJ bilaterally. All scans were acquired in closed (CM) and maximum mouth opening (MMO) positions. The difference in the volume of the oropharyngeal cavity obtained by subtracting the CM volume from the MMO volume (delta volume or volume variation) was calculated. The resulting volume was analyzed by Mann-Whitney test for variation in rotation. A significant difference was found ( -value = 0.0188) on the right side regarding changes in the rotational movement of the condyle (Mann-Whitney test). This study showed a relationship between degree of abnormal or limited rotation and variation in the upper airway volume on one side.